'From Childhood': A Markan Soteriology for Victims of Childhood Abuse. (August 2022) - O'Halloran, Nathan
In this article I bring an analysis of the boy possessed 'from childhood' in Mark 9:14–29 to bear on the contemporary situation of victims abused as children. I suggest that at least some of the discomfort we may feel in comparing an abused child to a possessed child in the Gospels stems from a residual feeling that demoniacs are guilty. But the Gospel witness is that possessed people are innocent and unwillingly 'colonized.' I then note the literary echoes between Mark 9:14–29 and Mark 14:32–42 which highlight Jesus' identification with victims in Gethsemane. I conclude by suggesting that the possessed boy of Mark 9 is representative of innocent childhood victims in his unwilling bondage, and that Jesus' salvific solidarity with him in Gethsemane offers to all victims of childhood abuse a healing space from which to identify with Christ on his healing journey toward resurrection.